PERANCANGAN APLIKASI PENGAJUAN CUTI KARYAWAN KEMENTERIAN AGAMA KOTA TEBING TINGGI - Permana, Nabilah Putri; Hendrik, , Billy (Smart Education, 2025)
Abstract: Leave is one of the entitlements provided by companies to employees. Matters related to leave and permissions are also regulated under Law No. 13 of 2003 concerning employment. Currently, the leave application process for employees at the Ministry of Religious Affairs in Tebing Tinggi is still conducted manually. Checking remaining leave balances, submitting leave requests, and approving leave are done in a hierarchical manner and still rely on paper-based leave archives. This leave management process has several weaknesses. Employees are unable to check their remaining leave balance, and another drawback is that the leave application process is inefficient and ineffective. The purpose of this study is to address the shortcomings of the current system while simplifying and accelerating the employee leave application process. In designing this leave application, the author uses modeling tools such as flow maps. The system approach method follows an object-oriented methodology, including Use Case Diagrams, Activity Diagrams, Class Diagrams, and Deployment Diagrams, along with database system design and user interface design. Keyword: Application; Employee Leave; Ministry of Religious Affairs; Web Abstrak: Cuti merupakan salah satu kewajiban perusahaan yang diberikan kepada karyawan. Hal mengenai perizinan dan cuti tersebut juga telah diatur dalam Undang-Undang No. 13 tahun 2003 tentang ketenagakerjaan. Proses aplikasi pengajuan cuti karyawan Kementerian Agama Tebing Tinggi saat ini masih dilakukan secara manual, pengecekan sisa cuti, pengajuan cuti dan persetujuan cuti dilakukan secara berjenjang dan masih mengandalkan arsip cuti berupa kertas. Proses pengelolaan cuti tersebut memiliki beberapa kelemahan. Pegawai tidak bisa mengetahui sisa hak cuti pribadi dan kelemahan yang lain adalah proses pengajuan cuti kurang efektif dan efisien. Tujuan dari penulisan ini adalah untuk memperbaiki kekurangan yang ada pada sistem yang berjalan saat ini serta mempermudah dan mempercepat proses pengajuan cuti karyawan. Pada perancangan aplikasi cuti ini penulis menggunakan alat pemodelan berupa flow map, metode pendekatan sistem menggunakan metode berorientasi objek yaitu Use Case Diagram, Activity Diagram, Class Diagram dan Deployment Diagram, rancangan sistem basis data dan rancangan antarmuka pengguna. Kata kunci: Aplikasi; Cuti Pegawai; Kementerian Agama; Web